Boron-Based Inhibitors of the NLRP3 Inflammasome. Issue 11 (16th November 2017) - Baldwin, Alex G.; Rivers-Auty, Jack; Daniels, Michael J.D.; White, Claire S.; Schwalbe, Carl H.; Schilling, Tom; Hammadi, Halah; Jaiyong, Panichakorn; Spencer, Nicholas G.; England, Hazel; Luheshi, Nadia M.; Kadirvel, Manikandan; et al.
Summary: NLRP3 is a receptor important for host responses to infection, yet is also known to contribute to devastating diseases such as Alzheimer's disease, diabetes, atherosclerosis, and others, making inhibitors for NLRP3 sought after. One of the inhibitors currently in use is 2-aminoethoxy diphenylborinate (2APB). Unfortunately, in addition to inhibiting NLRP3, 2APB also displays non-selective effects on cellular Ca 2+ homeostasis. Here, we use 2APB as a chemical scaffold to build a series of inhibitors, the NBC series, which inhibit the NLRP3 inflammasome in vitro and in vivo  without affecting Ca 2+ homeostasis. The core chemical insight of this work is that the oxazaborine ring is a critical feature of the NBC series, and the main biological insight the use of NBC inhibitors led to was that NLRP3 inflammasome activation was independent of Ca 2+ . The NBC compounds represent useful tools to dissect NLRP3 function, and may lead to oxazaborine ring-containing therapeutics. Graphical Abstract: Highlights: New inhibitors of the NLRP3 inflammasome are described NLRP3 inflammasome activation is independent of Ca 2+ These new inflammasome inhibitors are effective in vivo The inhibitors described may lead to the development of new drugs Abstract : The NLRP3 inflammasome is known to contribute to damaging inflammation during disease. Baldwin et al. describe a new boron-containing series of inflammasome inhibitors, which may lead to the development of new anti-inflammatory molecules and allow further interrogation of inflammatory mechanisms.